Pendidikan Keluarga dan Tanggung Jawab Keluarga - Ikhsan Ikhsan; Muhammad Hafid Abdi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Family education serves as the fundamental basis for shaping a child’s personality and character. As the first and foremost environment in a child’s life, the family plays a crucial role in instilling moral, social, religious, and cultural values that form the foundation of personal development. This study aims to examine the role and function of family education in character formation from an early age. The method used is a qualitative descriptive approach through literature review. The results show that families who actively carry out their educational role tend to raise children with positive character traits such as discipline, responsibility, and empathy. Family education proves to be a vital foundation before a child enters formal education. Keywords: family education, child character, parental role, moral values, personality development